Metal-organic frameworks based luminescent materials for nitroaromatics sensing - Zhang, Liangliang; Kang, Zixi; Xin, Xuelian; Sun, Daofeng (CrystEngComm, 2016)
Metal-organic frameworks (MOFs), composed of organic ligands and metal nodes, are well known for their high and permanent porosity, crystalline nature and versatile potential applications, which promoted them to be one of the most rapidly developing research focuses in chemical and materials science. During the various applications of MOFs, the photoluminescence properties of MOFs have received growing attention, especially for nitroaromatics (NACs) sensing, due to the consideration of homeland security, environmental cleaning and military issues. In this highlight, we summarize the progress in recent research in NACs sensing based on LMOFs cataloged by sensing techniques in the past three years, and then we describe the sensing applications for nano-MOF type materials and MOF film, together with MOF film applications. During the various applications of MOFs, the photoluminescence properties of MOFs have received growing attention, especially for nitroaromatics (NACs) sensing. In this highlight, we summarize the progress in recent research in NACs sensing based on MOFs and sensing applications for nano-MOF type materials and MOF film.